Quality Of Life in Epilepsy Patients: A cross sectional study - Aryal, S; Jha, A (Journal of Psychiatrists' Association of Nepal, 2020)
Introduction: The quality of life of people with epilepsy is hampered both by the nature of the disorder and its associated effects. This study was carried out to assess the quality of life in patients with epilepsy and determine the influence of various factors in quality of life in these patients. Material And Method: A cross sectional descriptive study was conducted in Mental Hospital, Lagankhel enrolling clinically diagnosed patients with epilepsy aged more than 18 years and on antiepileptic drugs for at least 6 months. Patients diagnosed with epilepsy but having mental retardation, overt cognitive impairment, psychiatric disorders or other co-morbid chronic systemic or neurological illnesses which could affect QOL were excluded from the study by detailed history, clinical examinations, previous medical records and relevant investigations. Results: Statistically significant differences in the quality of life scores were seen in terms of educational and marital status, and frequency of seizures within the last 6 months before evaluation. Statistically insignificant positive correlation was observed between the age of onset of seizures and the QOL scores. Similarly, statistically insignificant negative correlation observed between the number of drugs used and the QOL scores. Conclusion: Duration of epilepsy had a consistent negative effects on QOL. Evaluation of quality of life in epilepsy relatively measures the outcome for treatment for epilepsy.